Understanding others : peoples, animals, pasts - LaCapra, Dominick, 1939- (Ithaca : Cornell University Press, 2018)
'To what extent do we and can we understand others--other peoples, species, times, and places? What is the role of others within ourselves, epitomized in the notion of unconscious forces? Can we come to terms with our internalized others in ways that foster mutual understanding and counteract the tendency to scapegoat, project, victimize, and indulge in prejudicial and narcissistic impulses? How do various fields or disciplines address or avoid such questions? And, in the light of recent developments, have these questions become particularly pressing and not in the least confined to other peoples, times, and places? Making selective and critical use of the thought of such important figures as Sigmund Freud, Jacques Derrida, and Mikhail Bakhtin, the book investigates a series of crucial topics from the current state of deconstruction, trauma studies, and the humanities to newer fields such as animal studies and posthumanist scholarship. A feature of the book is the effort to bring critical historical thought into a provocative engagement with politics and our current political climate'--
History, deconstruction, and working through the past -- Humans, other animals, and the humanities -- Trauma, history, memory, identity : what remains? -- A Zuni artist answers back : Phil Hughte's cartoons on Frank Hamilton -- What is history? what is literature? -- What use are the humanities?.
Includes bibliographical references and index.
Keywords: Other (Philosophy).; Empathy -- Philosophy; Compassion -- Philosophy; Humanities -- Philosophy